Synthesis of biphenyl-based arsine ligands by Suzuki-Miyaura coupling and their application to Pd-catalyzed arsination - Uberman, Paula Marina (2011)
A versatile and efficient approach for the synthesis of new biphenyl-based arsine ligands, by a Pd-catalyzed arsination to introduce the -AsPh2 moiety, and then a Suzuki-Miyaura cross-coupling for biaryl construction is reported. By Pd-catalyzed arsination with n-Bu3SnAsPh2 (1), (2-bromophenyl)diphenylarsine (2, 83%) was obtained. The Suzuki-Miyaura reaction between the bromoarsine 2 and aryl boronic acids bearing different substituents provided biarylarsine ligands (80-99%). The efficiency of catalysts derived from the new biarylarsine ligands was evaluated in the Pd-catalyzed arsination with perfluoroalkyl iodides (RfI). Outstanding activities of catalysts derived from Pd/methoxybiarylarsine ligands were found in this coupling reaction affording perfluoroalkyl arsines in very good yields (57-100%). © 2011 The Royal Society of Chemistry.